2019
DOI: 10.1111/and.13300
|View full text |Cite
|
Sign up to set email alerts
|

Thiol–disulphide balance in infertility secondary to varicocele

Abstract: Oxidative stress plays an important role in the development of infertility secondary to varicocele. We aimed to investigate the dynamic thiol–disulphide homeostasis as an oxidative stress marker in the spermatic vein of infertility secondary to varicocele. Sixty‐one patients with varicocele were included in the study. Blood was drawn from the median cubital vein and the testicular venous return side before the spermatic vein was separated during surgery. Total thiol, native thiol, disulphide, ischaemia modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…They examined whether there was a difference in TDH markers between blood samples taken from spermatic and peripheral veins. They found that total and native thiol levels were statistically lower in blood taken from the spermatic vein (Coban et al, 2019). Gul and colleagues divided the patients into three groups as infertile with varicocele, fertile with varicocele and healthy fertile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They examined whether there was a difference in TDH markers between blood samples taken from spermatic and peripheral veins. They found that total and native thiol levels were statistically lower in blood taken from the spermatic vein (Coban et al, 2019). Gul and colleagues divided the patients into three groups as infertile with varicocele, fertile with varicocele and healthy fertile.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is a limited number of works reporting the relation between the varicocele and TDH (Coban et al, ; Gul et al, ; Sonmez et al, ). In the study of Coban et al, blood was drawn from spermatic and peripheral veins of 61 patients simultaneously during varicocelectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation